Sociālā pedagoga darbība 7.-9.klašu skolēnu pašaudzināšanas veicināšanā - Zariņa, Revita (Latvijas Universitāte, 2019)
Diplomdarba „Sociālā pedagoga darbība 7. - 9. klašu skolēnu pašaudzināšanas veicināšanā” mērķis ir raksturot sociālā pedagoga profesionālo darbību 7. - 9. klašu skolēnu pašaudzināšanas veicināšanā. Teorētiskajā daļā aprakstīta pašaudzināšanas būtība, pusaudžu vecumposma raksturojums pašaudzināšanas kontekstā un gribas nozīme pašaudzināšanas procesā. Praktiskajā daļā raksturots pētījums par pusaudžu izpratni par pašaudzināšanu. Tika izstrādāta sociālā pedagoga darba programma „Sociālā pedagoga darbība 7. - 9. klašu skolēnu pašaudzināšanas veicināšanā” un veikta programmas aprobācija un tās rezultātu analīze. Atslēgvārdi: griba, mērķtiecība, pašaudzināšana, pašizziņa.

Diploma paper „Activity of the Social Pedagogue Facilitate Self-development of Students in Grades 7 - 9” is developed with the aim to characterize the social pedagogue activity in promoting the self- development of students in grades 7 - 9. In the theoretical part there is described the essence of self-education, its characterization and specific features in adolescence, the social pedagogical activity for setting and achieving the goal of self-education, the importance of will self-education, the control and evaluation of the process of self-education The practical part describes a study of teenagers' understanding of self-education. The social pedagogue activity program “Social pedagogue activity in promoting self- development of 7th - 9th grade students” was developed. There is carried out the approbation of the program and analysis of its results. Keywords: purposefulness, self-education, self-study, will.
Activity of the Social Pedagogue Facilitate Self-development of Students in Grades 7 - 9”
Keywords: Pedagoģija; griba; mērķtiecība; pašaudzināšana; pašizziņa